Supply Chain Management In Algerian Companies: The Need For Partnerships With Suppliers - Lachache, Abdelhalim (جامعة الوادي - University of Eloued, 2020)
The aim of this study is to clarify the effective role of companies to manage supply chain to achieve partnerships with suppliers. The approach of supply chain management has great importance to economic companies, so it is necessary to deal with the adoption of supply chain management. As well as we will show the importance of the suppliers as a dynamic element in the supply chain. So it is necessary to clarify the interaction between supply chain management and suppliers. To illustrate this, we conducted a field study in a group of Algerian companies. We used the questionnaire as a tool to analyze the data we obtained using the SPSS program. This study found that the efficient management of supply chain leads the company to achieve partnerships with suppliers.
مقال
Keywords: Supply Chain Management ; Suppliers ; Efficiency ; Partnerships